A note on the transcendental status of beauty - Vijgen, Jörgen (Sapientia, 2004)
The status of beauty as a transcendental in the works of St. Thomas has been a subject of heated controversy among Thomists. Since it is not included in the famous derivation of the five transcendental properties of ens in De veritate 1, 1, many Thomists have been undecided regarding its status, or simply have not raised the question. Others have vehemently either denied or defended the transcendentality of beauty. An indication of the complexity of this controversy is the fact that all these different posiiions can be found in the writings of the members of the so-called School of Louvain. For instante, Ferdinand van Steenberghen explicitly rejected its transcendental status, following the position of his master Maurice de Wulf. At the same time Louis De Raeymaeker, the future president of the Higher Institute for Philosophy, first defended the transcendental status of beauty in his Metaphysica generalis but a decade later he appears to have a more moderate position, in the sense that he does not mention beauty among the transcendentals.